Circularly polarized luminescent systems fabricated by Tröger's base derivatives through two different strategies - Qian, Cheng; Chen, Yuan; Zhao, Qian; Cheng, Ming; Lin, Chen; Jiang, Juli; Wang, Leyong (Beilstein Journal of Organic Chemistry, 2021)
The Tröger's base derivative rac-TBPP was synthesized and separated into two enantiomers R2N-TBPP and S2N-TBPP by chiral column chromatography. These compounds show a strong circularly polarized luminescence with glum values of +0.0021, and −0.0025, respectively. The second way to fabricate the rac-TBPP-based CPL-active material is to co-gel the fluorescent rac-TBPP with a chiral ᴅ-glutamic acid gelator DGG by co-assembly strategy. At the molar ratio of rac-TBPP/DGG = 1:80, the glum value of the co-gel was about three times higher than the glum values of R2N-TBPP and S2N-TBPP enantiomers. Interestingly, the CPL handedness of the rac-TBPP/DGG co-gel could be adjusted effectively by changing their stoichiometric ratios.
Keywords: circularly polarized luminescence; chiral resolution; co-gelation; inversion of CPL handedness; Tröger's base

(untitled) - Zhang, Z.-Y.; Chen, Y.; Liu, Y. (Angew. Chem., Int. Ed., 2019)

(untitled) - Chen, C.; Chi, Z.; Chong, K. C.; Batsanov, A. S.; Yang, Z.; Mao, Z.; Yang, Z.; Liu, B. (Nat. Mater., 2020)

(untitled) - Bolton, O.; Lee, K.; Kim, H.-J.; Lin, K. Y.; Kim, J. (Nat. Chem., 2011)

(untitled) - Zhao, Z.; Zhang, H.; Lam, J. W. Y.; Tang, B. Z. (Angew. Chem., Int. Ed., 2020)

(untitled) - Li, J.; Wang, J.; Li, H.; Song, N.; Wang, D.; Tang, B. Z. (Chem. Soc. Rev., 2020)

(untitled) - Roose, J.; Tang, B. Z.; Wong, K. S. (Small, 2016)

(untitled) - Han, J.; Guo, S.; Lu, H.; Liu, S.; Zhao, Q.; Huang, W. (Adv. Opt. Mater., 2018)

(untitled) - Zheng, H.; Li, W.; Li, W.; Wang, X.; Tang, Z.; Zhang, S. X.-A.; Xu, Y. (Adv. Mater. (Weinheim, Ger.), 2018)

(untitled) - Nitti, A.; Pasini, D. (Adv. Mater. (Weinheim, Ger.), 2020)

(untitled) - Han, J.; You, J.; Li, X.; Duan, P.; Liu, M. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Berova, N.; Bari, L. D.; Pescitelli, G. (Chem. Soc. Rev., 2007)

(untitled) - Sánchez-Carnerero, E. M.; Agarrabeitia, A. R.; Moreno, F.; Maroto, B. L.; Muller, G.; Ortiz, M. J.; de la Moya, S. (Chem. – Eur. J., 2015)

(untitled) - Rúnarsson, Ö. V.; Artacho, J.; Wärnmark, K. (Eur. J. Org. Chem., 2012)

(untitled) - Dolenský, B.; Havlík, M.; Král, V. (Chem. Soc. Rev., 2012)

(untitled) - Tröger, J. (J. Prakt. Chem., 1887)

(untitled) - Yuan, C.-X.; Tao, X.-T.; Ren, Y.; Li, Y.; Yang, J.-X.; Yu, W.-T.; Wang, L.; Jiang, M.-H. (J. Phys. Chem. C, 2007)

(untitled) - Xi, H.; Liu, Y.; Yuan, C.-X.; Li, Y.-X.; Wang, L.; Tao, X.-T.; Ma, X.-H.; Zhang, C.-F.; Hao, Y. (RSC Adv., 2015)

(untitled) - Yuan, R.; Li, M.-q.; Xu, J.-b.; Huang, S.-y.; Zhou, S.-l.; Zhang, P.; Liu, J.-j.; Wu, H. (Tetrahedron, 2016)

(untitled) - Sang, Y.; Han, J.; Zhao, T.; Duan, P.; Liu, M. (Adv. Mater. (Weinheim, Ger.), 2020)

(untitled) - Takaishi, K.; Iwachido, K.; Takehana, R.; Uchiyama, M.; Ema, T. (J. Am. Chem. Soc., 2019)

(untitled) - Liang, J.; Guo, P.; Qin, X.; Gao, X.; Ma, K.; Zhu, X.; Jin, X.; Xu, W.; Jiang, L.; Duan, P. (ACS Nano, 2020)

(untitled) - Yuan, C.; Zhang, Y.; Xi, H.; Tao, X. (RSC Adv., 2017)

(untitled) - Chen, Y.; Cheng, M.; Hong, B.; Zhao, Q.; Qian, C.; Jiang, J.; Li, S.; Lin, C.; Wang, L. (Front. Chem. (Lausanne, Switz.), 2019)

(untitled) - Riehl, J. P.; Richardson, F. S. (Chem. Rev., 1986)

(untitled) - Ma, J.-L.; Peng, Q.; Zhao, C.-H. (Chem. – Eur. J., 2019)

(untitled) - Bachl, J.; Mayr, J.; Sayago, F. J.; Cativiela, C.; Díaz Díaz, D. (Chem. Commun., 2015)

(untitled) - Li, P.; Lü, B.; Han, D.; Duan, P.; Liu, M.; Yin, M. (Chem. Commun., 2019)